A case report of didelphys uterus with right obstruction of cervix due to transverse vaginal septum - Firoozeh Ahmadi; Fattaneh Pahlavan (Mashhad University of Medical Sciences, 2020)
Introduction: Didelphys uterus is found in 0.1% to 0.5% of women in reproductive age. Imaging plays an important role in the diagnosis of this anomaly. This study was parformed with aim to train the stages for diagnosing of a rare case of didelphys uterus accompany with obstruction of the cervix due to transverse vaginal septum. Case presentation: A 25 - years - old woman with infertility, history of irregular menstruation, dysmenorrhea, prolanged bleeding and spotting was admited in the infertility ward of the Royan Institute. Vaginal examination revealed a 3 cm mass in the right part of the vagina. The uterus was observed as didelphys along with a 43 mm hypo-echo mass in the right and lower part of the uterus. In hysterosalpingography, the uterus has a unicorn view. According to this result and sonography findings, didelphys uterus with right obstruction of cervix was reported. MRI also confirmed these findings. A connection was made between two uterine cavities with Strasman surgery, but the patient's symptoms persisted and cysts containing secretions and blood clots were still seen on ultrasound. Due to the persistence of hematocolposus, septum of the vagin was removed and obstruction was eliminated and all clinical symptoms of the patient were removed. Conclusion: Two and Three Dimensional Ultrasound, hysterosalpingography and MRI play an important role in the diagnosis of uterine anomalies, including didelphys uterus.